PENERAPAN GAYA KEPEMIMPINAN TRANSFORMING BRANCH MANAGER KCP BANK SYARIAH - Harbani, Harbani; Amansyah, Farida; Yahya, Andi; Sari, Mawar (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2024)
This research was aimed to determine how the implementation Transforming Leadership Style Impelementation of Branch Manager KCP Indonesian Islamic Bank Tamalanrea 1 Makassar for the period of 2021-2024.The research method used was descriptive research. The sampling technique used was saturated sampling technique where the entire 23 population were taken as samples. Measurement of data was using a likert scale and data collection methods through observation, questionnaires dan interviews. The data analysis used was quantitative analysis supported by qualitative analysis and data processing using frequency distribution table.Based on the research which has been done, the results were the implementation of the Transforming Leadership of Branch Manager Indonesian Islamic Bank Tamalanrea 1 Makassar for the Period 2021-2024 shows a total 120 (34.09%) where this value is in the highest score range with the interpretation of